A Large New Crater Exposes the Limits of Water Ice on Mars - Dundas, C.M.; Mellon, M.T.; Posiolova, L.V.; Miljković, Katarina; Collins, G.S.; Tornabene, L.L.; Rangarajan, V.G.; Golombek, M.P.; Warner, N.H.; Daubar, I.J.; Byrne, S.; McEwen, A.S.; et al. (AMER GEOPHYSICAL UNION, 2023)
Water ice in the Martian mid-latitudes has advanced and retreated in response to variations in the planet's orbit, obliquity, and climate. A 150 m-diameter new impact crater near 35°N provides the lowest-latitude impact exposure of subsurface ice on Mars. This is the largest known ice-exposing crater and provides key constraints on Martian climate history. This crater indicates a regional, relatively pure ice deposit that is unstable and has nearly vanished. In the past, this deposit may have been tens of meters thick and extended equatorward of 35°N. We infer that it is overlain by pore ice emplaced during temporary stable intervals, due to recent climate variability. The marginal survival of ice here suggests that it is near the edge of shallow ice that regularly exchanges with the atmosphere.